An infrastructure model for smart cities based on big data. (2018) - Gomes, Eliza H.A.; Dantas, Mario A.R.; Macedo, Douglas D.J. De; Rolt, Carlos R. De; Dias, Julio; Foschini, Luca
The massive amount of data generated in projects focused on smart cities creates a degree of complexity in how to manage all this information. In attention to solve this problem, several approaches have been developed in recent years. In this paper we propose an infrastructure model for big data for a smart city project. The goal of this model is to present the stages for the processing of data in the steps of extraction, storage, processing and visualisation, as well as the types of tools needed for each phase. To implement our proposed model, we used the ParticipACT Brazil, which is a project based in smart cities. This project uses different databases to compose its big data and uses this data to solve urban problems. We observe that our model provides a structured vision of the software to be used in big data server of ParticipACT Brazil.